Análisis de los puntajes obtenidos en la prueba Saber Pro por los estudiantes de la Universidad de Pamplona, Colombia, durante el año 2020 - Stefany Yarick Toncel-Ramos; Nixon Albeiro Zambrano-Medina; Mayerly Llanos-Redondo; Heriberto Rangel-Navia Rangel-Navia; Andrés Llanos-Redondo (Mundo Fesc)
The Colombian National Exam for the Quality of Higher Education, Saber Pro, is proposed as a tool for assessing quality. This exam is intended for students who complete undergraduate studies and must meet this requirement for graduation. It consists of a set of generic competencies that evaluate critical reading, quantitative reasoning, citizenship skills, written communication, and English. Various studies relate the intellectual capacity, sociodemographic, and academic factors of high- and low-performing students on the exam. The research aimed to conduct a comparative study of the average scores in the generic competencies of the 2020 Saber Pro tests of the seven faculties of the University of Pamplona. Data from 3,905 students were included. An ANOVA was performed to compare the average scores for each of the modules, finding statistically significant differences in the analyzed averages. Both the a posteriori test used (Duncan test) as well as the overall averages obtained by faculty, reveal that the Faculty of Basic Sciences was the one that stood out the most, followed by the Faculty of Health, then followed by the Faculties of Engineering and Architecture, Arts and Humanities, and Agricultural Sciences, with the Faculties of Educational Sciences and Economic and Business Sciences obtaining the lowest average scores. The Faculty of Basic Sciences stands out in quantitative reasoning with a score of (163.26) followed by civic skills, critical reading and English, with written communication being the module where the lowest scores were obtained (137.09).